Diversity-oriented synthesis of dihydrobenzoxazepinones by coupling the Ugi multicomponent reaction with a Mitsunobu cyclization - Moni, Lisa (Beilstein-Institut, 2014)
An operationally simple protocol for the synthesis of 2,3-dihydrobenzo[f][1,4]oxazepin-3-ones, based on an Ugi reaction of an ortho-(benzyloxy)benzylamine, glycolic acid, an isocyanide and an aldehyde, followed by an intramolecular Mitsunobu substitution was developed. The required ortho-(benzyloxy)benzylamines have been in situ generated from the corresponding azides, in turn prepared in high yields from salicylic derivatives.